Implikasi corporate governance, investment opportunity set, firm size, dan leverage terhadap earnings quality - Nariman, Augustpaosa; Ekadjaja, Margarita (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2018)
Profit of a company is used by creditor and investor to evaluate the performance of the management, estimate earnings power, and to predict future profit. Earning qualityis measured from the accrual. A company with high accrual is indicating that the quality of company profit is low, and vice versa. According to Chan,et al. (2001) profit quality in the financial report will increase company value which is reflected in the stock return. Purpose of the this research is to understand the impact of variable ofinstitutional shareholding, board size, board independence, investment opportunity set, firm size, and leverageto theearnings quality.Â This research is using manufacturing industry that listed in the Indonesian stock exchange during the period of 2013-2016,sample is taken using purposive samplin technique.Based on analysis result and research is done using double linear regression with the eviews 9.0 software, we can conclude that there is a significant positive influence between institutional shareholding, board size, board independence, investment opportunity set, firm size, and leverageto the earnings quality. While leverage has insignificant influence to the earnings qualitymeasured with Discretionary Accruals (DACCR).